Rowley jefferson's awesome friendly adventure ebook - Kinney, Jeff (2020)
An instant #1 New York Times bestseller! You've never seen the Wimpy Kid World like this before—an entirely new, awesome, friendly, truly fantastic fantasy quest from #1 international bestselling author Jeff Kinney! From the imagination of Rowley Jefferson comes an adventure of epic proportions. Join Roland and his best friend, Garg the Barbarian, as they leave the safety of their village and embark on a quest to save Roland's mom from the White Warlock. Will our heroes survive? Find out in Rowley Jefferson's Awesome Friendly Adventure ! And don't miss Rowley Jefferson's first book, the instant #1 bestseller , Diary of an Awesome Friendly Kid: Rowley Jefferson's Journal !